2021
DOI: 10.1007/s11356-021-12969-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: a new emerging respiratory disease from the neurological perspective

Abstract: Coronavirus disease 2019 (COVID-19) has become a challenging public health catastrophe worldwide. The newly emerged disease spread in almost all countries and infected 100 million persons worldwide. The infection is not limited to the respiratory system but involves various body systems and may lead to multiple organ failure. Tissue degenerative changes result from direct viral invasion, indirect consequences, or through an uncontrolled immune response. Severe acute respiratory syndrome coronavirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 142 publications
(135 reference statements)
0
17
0
3
Order By: Relevance
“…Ein Angriffspunkt des Virus ist der ACE2-Rezeptor, der zum einen als Eintrittspforte dienen, jedoch auch durch eine endotheliale Entzündungsreaktion die Blut-Hirn-Schranke direkt beeinflussen kann [6]. Eintrittspforten in das zentrale Nervensystem können transsynaptisch über den N. olfactorius, hämatogen mittels rezeptorvermittelter Transzytose, indirekt hämatogen über infizierte Leukozyten und retrograd neurogen über periphere oder gastrointestinale Nervenendigungen bestehen [7].…”
Section: Pathophysiologische Mechanismenunclassified
“…Ein Angriffspunkt des Virus ist der ACE2-Rezeptor, der zum einen als Eintrittspforte dienen, jedoch auch durch eine endotheliale Entzündungsreaktion die Blut-Hirn-Schranke direkt beeinflussen kann [6]. Eintrittspforten in das zentrale Nervensystem können transsynaptisch über den N. olfactorius, hämatogen mittels rezeptorvermittelter Transzytose, indirekt hämatogen über infizierte Leukozyten und retrograd neurogen über periphere oder gastrointestinale Nervenendigungen bestehen [7].…”
Section: Pathophysiologische Mechanismenunclassified
“…As of June 30, 2021, over 180 million cases of COVID-19 have been reported, and more than 3.9 million lives claimed worldwide ( https://covid19.who.int/ ). Due to its fast spread and high mortality rate, scientists have worked on all fronts to characterize the virus ( El-Sayed and Kamel, 2021 ; Harrison et al, 2020 ; Yao et al, 2020 ) and reported clinical symptoms associated with the viral disease ( El-Sayed et al, 2021a , El-Sayed et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Human activities have dramatically impacted earth’s environment. Modern human society has increased health and longevity, but has created the conditions for emergence of new pathogens and their rapid spread across the globe (El-Sayed et al 2021 ). Several recent publications have proved the close connection between the environment and the COVID-19 pandemic from different perspectives, including the impact of human activities.…”
mentioning
confidence: 99%